The Development of Village-Owned Enterprises Through the Empowerment of Village Assets in Kuwaron Village, Gubug District, Grobogan Regency, Central Java - Sulistyowati, Sulistyowati; Mastoah, Siti; Prasetyo, Mas Subagyo Eko; Maharani, Dewi Nadya (LAW FACULTY UNISSULA, 2024)
Kuwaron village, Gubug District, Grobogan Regency, Central Java, is one of the villages that wants to improve the ranking of maju mandiri villages, such as efficient village asset management to get Village income through village-owned enterprises (BUMDes). Demographically, the population's livelihood is that of farmers. The natural conditions of the village are very potential for the development of village-owned enterprises. The village government's main problem is managing village-owned enterprises with the potential to be owned by the village. This research used normative research. The primary substance for Village-owned enterprises is how to organize and manage the creative economy based on the potential and assets of the village. However, this cannot be done optimally because the Kuwaron village government and the management of village-owned enterprises still face some obstacles. This activity aims to strengthen, enlighten, and open up insight into the rules of law related and closely related to the management of village-owned enterprises so that they can institutionally synchronize the formulation and determination of asset management policies following the village's potential. Moving on from these objectives, the methods used in this activity are legal counseling on village asset management for developing village-owned enterprises.